2008
DOI: 10.1164/rccm.200801-131oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 as a Stratification Tool for Interventional Trials Involving Pediatric Septic Shock

Abstract: Rationale: Interventional clinical trials involving children with septic shock would benefit from an efficient preenrollment stratification strategy. Objectives: To test the predictive value of interleukin (IL)-8 for 28-day mortality in pediatric septic shock. Methods: A training data set (n 5 40) identified a serum IL-8 of greater than 220 pg/ml as having a 75% sensitivity and specificity for predicting 28-day mortality. This cutoff was then subjected to a series of validation steps. Measurements and Main Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 39 publications
5
104
2
4
Order By: Relevance
“…In agreement with these results, the HH/LC phenotype induced a signifi cantly higher release of the proinfl ammatory chemokine IL-8 than did the LH/HC phenotype. Considering the strong association between IL-8 serum levels and severity of sepsis (33,34), as well as the previously reported contribution of the β-h/c to the severe manifestations of septicemia in animal models (13,(35)(36)(37), we compared the isolates in an in vivo sepsis model. Indeed, in a high-dose sepsis model in mice, the HH/LC phenotypic variant was associated with accelerated death, although blood CFU levels were lower than observed with the LH/ HC variant.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these results, the HH/LC phenotype induced a signifi cantly higher release of the proinfl ammatory chemokine IL-8 than did the LH/HC phenotype. Considering the strong association between IL-8 serum levels and severity of sepsis (33,34), as well as the previously reported contribution of the β-h/c to the severe manifestations of septicemia in animal models (13,(35)(36)(37), we compared the isolates in an in vivo sepsis model. Indeed, in a high-dose sepsis model in mice, the HH/LC phenotypic variant was associated with accelerated death, although blood CFU levels were lower than observed with the LH/ HC variant.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that serum IL-8 protein levels, measured within 24 hours of presentation to the intensive care unit with septic shock, could predict survival in pediatric septic shock with a probability of 95% [54]. The ability of IL-8 to serve as a stratification biomarker was subsequently validated in a completely independent cohort of children with septic shock.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…Maintained elevated PCT values over a period of time identify a worsening of the inflammatory process due to the lack of septic shock control. Interleukin-8 can also predict outcome in pediatric septic shock with high negative but unacceptably low positive predictive values for mortality [11]. Other currently available clinical markers such as vasopressin and copeptin were not found to have utility for severity and outcome prediction in pediatric septic shock [12].…”
mentioning
confidence: 97%